Enhancing Awareness and Management of Carpal Tunnel Syndrome Among Medical Professionals and Athletes - Makuch, Rafał; Chrościcka, Alicja; Gała, Kamil; Czajka, Andrzej; Lenard, Paweł; Kucharski, Adam; Michalska, Sara; Pilarski, Konrad; Dewicka, Martyna; Wawrzyniak, Alicja Maria (Quality in Sport, 2024)
Introduction and objective: The objective of this research is to enhance the awareness of carpal tunnel among medical professionals and individuals engaged in sports. The acquired knowledge will enable medical professionals to more effectively identify, treat, and prevent issues related to carpal tunnel. Additionally, individuals engaged in sports will be able to prevent the occurrence of carpal tunnel syndrome in themselves or their pupils, thereby allowing them to engage in long-term and safe physical activity. Review methods: Review and summary of research studies available in open-source format on Google Scholar, PubMed. Abbreviated description of the state of knowledge: Carpal tunnel syndrome is a disease belonging to the group of compression neuropathies. The symptoms of carpal tunnel syndrome typically manifest as an uncomfortable sensation in the thumb, index finger, and half of the ring finger. Such symptoms may include numbness and tingling. In some cases, weakness of the hand muscles may occur, and in rarer instances, atrophy of the hand muscles. The condition of carpal tunnel syndrome is primarily the result of repetitive movements of the fingers and wrist. Such activities include typing, using a mouse, riding a bicycle, or playing a musical instrument. Summary: Carpal tunnel syndrome is a prevalent condition among the general population. This condition may affect individuals who engage in regular physical activity, resulting in diminished efficiency and a notable reduction in the quality of life. The objective of this study is to examine the risk factors, symptoms, and diagnostic methods associated with carpal tunnel syndrome. In the context of sports, we will examine the mechanisms of disease development in athletes and focus on prevention. This encompasses the rehabilitation of individuals at risk of developing the disease and patient education, which will facilitate the minimisation of the appearance or recurrence of disease symptoms.